Cellular and transcriptional impacts of Janus kinase and/or IFN-gamma inhibition in a mouse model of primary hemophagocytic lymphohistiocytosis - Albeituni, Sabrin; Oak, Ninad; Tillman, Heather S.; Stroh, Alexa; Keenan, Camille; Bloom, Mackenzie; Nichols, Kim E. (Frontiers in Immunology, 2023)
Background Primary hemophagocytic lymphohistiocytosis (pHLH) is an inherited inflammatory syndrome driven by the exuberant activation of interferon-gamma (IFNg)-producing CD8 T cells. Towards this end, ruxolitinib treatment or IFNg neutralization (aIFNg) lessens immunopathology in a model of pHLH in which perforin-deficient mice (Prf1–/–) are infected with Lymphocytic Choriomeningitis virus (LCMV). However, neither agent completely eradicates inflammation. Two studies combining ruxolitinib with aIFNg report conflicting results with one demonstrating improvement and the other worsening of disease manifestations. As these studies used differing doses of drugs and varying LCMV strains, it remained unclear whether combination therapy is safe and effective. Methods We previously showed that a ruxolitinib dose of 90 mg/kg lessens inflammation in Prf1–/– mice infected with LCMV-Armstrong. To determine whether this dose controls inflammation induced by a different LCMV strain, we administered ruxolitinib at 90mg/kg to Prf1–/– mice infected with LCMV-WE. To elucidate the impacts of single agent versus combination therapy, Prf1–/– animals were infected with LCMV, treated or not with ruxolitinib, aIFNg or both agents, and analyzed for disease features and the transcriptional impacts of therapy within purified CD8 T cells. Results Ruxolitinib is well-tolerated and controls disease regardless of the viral strain used. aIFNg, administered alone or with ruxolitinib, is most effective at reversing anemia and reducing serum IFNg levels. In contrast, ruxolitinib appears better than aIFNg, and equally or more effective than combination therapy, at lessening immune cell expansion and cytokine production. Each treatment targets distinct gene expression pathways with aIFNg downregulating IFNg, IFNa, and IL-6-STAT3 pathways, and ruxolitinib downregulating IL-6-STAT3, glycolysis, and reactive oxygen species pathways. Unexpectedly, combination therapy is associated with upregulation of genes driving cell survival and proliferation. Conclusions Ruxolitinib is tolerated and curtails inflammation regardless of the inciting viral strain and whether it is given alone or in combination with aIFNg. When administered at the doses used in this study, the combination of ruxolitinb and aIFNg appears no better than treatment with either drug alone in lessening inflammation. Further studies are warranted to elucidate the optimal doses, schedules, and combinations of these agents for the treatment of patients with pHLH.